Pola Sebaran Ruang Terbuka Hijau (RTH) Publik di Kota Balikpapan Berdasarkan Jenis dan Karakteristiknya - Ajeng Nugrahaning Dewanti; Mega Ulimaz; Ariyaningsih Ariyaningsih (JST (Jurnal Sains Terapan), 2018)
Balikpapan City has a population that continues to increase in 2010 to 2015. Population growth has resulted in population densification and rapid and uncontrolled settlements in parts of the city. Thus, the need for space to accommodate population growth will increase so that it is very vulnerable to changes in the use of green open space into settlements and built area. The Changes in land use functions will have a negative impact on environmental conditions if did not controlled. Thus, it is necessary to control land use in terms of green open space availability which begins with analyzing the distribution patterns, types and characteristics of each green open space. The purpose of this study was to analyze the distribution patterns of public green open spaces based on their types and characteristics. As for the analysis carried out to achieve this goal there are several stages. First, identification of the distribution of public green open space based on its type through field observation; second, an analysis of the distribution of public green open space related to the type is carried out through literature studies and field observations. Finally, analyze the characteristics of each public green open space using statistical descriptive method.Keywords:  public green open space, types, characteristic